MECHANICAL PROPERTIES OF MATERIALS USED IN DENTISTRY - Akhrorov Ma’ruf Nasimjonovich (Modern American Journals, 2025)
This study aims to analyze the key physical and mechanical properties of materials commonly used in dentistry. These properties significantly influence the clinical performance and longevity of dental restorations and prostheses. Physical characteristics such as melting and boiling points, linear stress, thermal conductivity, thermal expansion coefficients, optical constants, color, and phase transitions are examined. In addition, mechanical properties including strength, hardness, elasticity, ductility, flowability, and brittleness are discussed in detail. Strength is defined as the ability to withstand external force without destruction, while elasticity refers to the material’s ability to recover its shape after deformation. Ductility and viscosity determine how materials behave under continuous stress or rapid load application. The study highlights how these characteristics impact material selection in clinical dental applications. Understanding these properties allows dental professionals to make evidence-based decisions when choosing restorative materials for optimal patient outcomes.
Keywords: Elasticity, hardness, strength, deformation, force, pressure, ductility, viscosity, fracture, prosthesis